2015
DOI: 10.1002/biot.201500327
|View full text |Cite
|
Sign up to set email alerts
|

Valeric acid induces cell cycle arrest at G1 phase in CHO cell cultures and improves recombinant antibody productivity

Abstract: To find a more effective chemical reagent for improved monoclonal antibody (mAb) production, eight chemical reagents (curcumin, quercein, DL-sulforaphane, thymidine, valeric acid, phenyl butyrate, valproic acid, and lithium chloride) known to induce cell cycle arrest were examined individually as chemical additives to recombinant CHO (rCHO) cell cultures producing mAb. Among these chemical additives, valeric acid showed the best production performance. Valeric acid decreased specific growth rate (μ), but incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“…The rCHO cell line producing rituximab (SM-0.025) was established by transfection of a vector containing glutamine synthetase (GS) and antibody genes into GS knockout CHO-K1 cells using Lipofectamine 2000 (Invitrogen, Carsbad, CA), following the manufacturer’s protocols, and subsequent selection using 25 μM methionine sulfoximine (MSX, Sigma-Aldrich, St. Louis, MO)47. SM-0.025 cells were adapted to grow in a serum-free suspension culture in 125 mL Erlenmeyer flasks (Corning, Corning, NY) containing 50 mL of culture medium and incubated in a climo-shaking incubator (ISF1-X, Adolf Kuhner AG, Birsfelden, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…The rCHO cell line producing rituximab (SM-0.025) was established by transfection of a vector containing glutamine synthetase (GS) and antibody genes into GS knockout CHO-K1 cells using Lipofectamine 2000 (Invitrogen, Carsbad, CA), following the manufacturer’s protocols, and subsequent selection using 25 μM methionine sulfoximine (MSX, Sigma-Aldrich, St. Louis, MO)47. SM-0.025 cells were adapted to grow in a serum-free suspension culture in 125 mL Erlenmeyer flasks (Corning, Corning, NY) containing 50 mL of culture medium and incubated in a climo-shaking incubator (ISF1-X, Adolf Kuhner AG, Birsfelden, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, gene regulation and culture condition optimization has also been used to induce G1 phase arrest during cell cycle to improve cellular metabolism [38, 39]. Different from those previous studies, the comparative proteomics in our study has identified some cytoskeletal proteins (i.e.…”
Section: Resultsmentioning
confidence: 79%
“…Thus, we investigated whether the compounds influenced cell cycle progression. Several studies have shown that an increase of cells in G1 phase correlates with higher recombinant protein levels in stable CHO cell lines . For transient gene expression, Tait et al, showed that luciferase activity and hence luciferase expression increased in CHO cells upon treatment with cell cycle arresting agents (nocodazole: G2/M arrest; hydroxyurea: G1 arrest) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that an increase of cells in G1 phase correlates with higher recombinant protein levels in stable CHO cell lines. 12,17,20 For transient gene expression, Tait et al, showed that luciferase activity and hence luciferase expression increased in CHO cells upon treatment with cell cycle arresting agents (nocodazole: G2/M arrest; hydroxyurea: G1 arrest). 36 Furthermore, coexpression of the cell cycle regulators p18, p21, and p27, which induce G1 arrest, 37 was found to improve antibody expression in HEK293E and CHO cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation